2020
DOI: 10.1016/j.annonc.2020.08.2335
|View full text |Cite
|
Sign up to set email alerts
|

NRG1 fusion-driven tumors: biology, detection, and the therapeutic role of afatinib and other ErbB-targeting agents

Abstract: Oncogenic gene fusions are hybrid genes that result from structural DNA rearrangements, leading to deregulated activity. Fusions involving the neuregulin-1 gene (NRG1) result in ErbB-mediated pathway activation and therefore present a rational candidate for targeted treatment. The most frequently reported NRG1 fusion is CD74-NRG1, which most commonly occurs in patients with invasive mucinous adenocarcinomas (IMAs) of the lung, although several other NRG1 fusion partners have been identified in patients with lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
95
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 82 publications
(179 reference statements)
1
95
1
1
Order By: Relevance
“…Fusions of NRG1, the activating ligand of HER3, are rare genomic alterations found in 0.2%-0.5% of all solid tumors and have been identi ed in > 10 unique tumor types [14,15]. Since the completion of this study, our knowledge of NRG1 fusions and their role in HER3 tumor biology has expanded notably, along with the increasing number of NRG1 fusion partners identi ed across multiple solid tumor types [11,16,17]. Per current understanding, HER3 overactivation by NRG1 fusion proteins represents the primary driver of growth and survival in tumors harboring NRG1 fusions [16][17][18], and the presence (vs. absence) of NRG1 fusions has been shown to correlate with worsened survival outcomes in lung cancer, including shorter overall survival and disease-free survival [19].…”
Section: Discussionmentioning
confidence: 91%
“…Fusions of NRG1, the activating ligand of HER3, are rare genomic alterations found in 0.2%-0.5% of all solid tumors and have been identi ed in > 10 unique tumor types [14,15]. Since the completion of this study, our knowledge of NRG1 fusions and their role in HER3 tumor biology has expanded notably, along with the increasing number of NRG1 fusion partners identi ed across multiple solid tumor types [11,16,17]. Per current understanding, HER3 overactivation by NRG1 fusion proteins represents the primary driver of growth and survival in tumors harboring NRG1 fusions [16][17][18], and the presence (vs. absence) of NRG1 fusions has been shown to correlate with worsened survival outcomes in lung cancer, including shorter overall survival and disease-free survival [19].…”
Section: Discussionmentioning
confidence: 91%
“…Previously, in vitro studies have shown that NRG1 fusion genes are oncogenic drivers, and NRG1 rearranged carcinomas could be sensitive to the ERBB2 and the new generation of ERBB3 targeting therapies 15,27,28 . Currently, dozens of molecules aiming at ERBB2 and ERBB3 are being clinically tested 24,28‐31 . Thus, it is worth identifying the patients with NRG1 fusion carcinomas providing them with the pathway to targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The screening strategy is not established so far. NRG1 rearranged tumors are enriched (reportedly 7%‐31%) in lung invasive mucinous adenocarcinomas followed by pancreatobiliary system, ovary, breast, and rare findings in other locations 8,21,25,26,31‐34 . Possibly, lung (invasive mucinous) adenocarcinomas or less specifically NSCLC could be the most suitable for starting a routine NRG1 rearrangement testing followed by the other organ sites including pancreas and prostate 20,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations